Genetic marker-based multi-locus sequence analysis for classification, genotyping, and phylogenetics of the family Bifidobacteriaceae as an alternative approach to phylogenomics - Mekadim, Chahrazed; Bunešová, Věra; Vlková, Eva; Hroncová, Zuzana; Killer, Jiří (Antonie van Leeuwenhoek, 2019)
Bifidobacteria are widely known for their probiotic potential; however, little is known regarding the ecological significance and potential probiotic effects of the phylogenetically related 'scardovial' genera (Aeriscardovia, Alloscardovia, Bombiscardovia, Galliscardovia, Neoscardovia, Parascardovia, Pseudoscardovia and Scardovia) and Gardnerella classified with bifidobacteria within the Bifidobacteriaceae family. Accurate classification and genotyping of bacteria using certain housekeeping genes is possible, whilst current phylogenomic analyses allow for extremely precise classification. Studies of applicable genetic markers may provide results comparable to those obtained from phylogenomic analyses of the family Bifidobacteriaceae. Segments of the glyS (624 nucleotides), pheS (555 nucleotides), rpsA (630 nucleotides), and rpsB (432 nucleotides) genes and their concatenated sequence were explored. The mean glyS, pheS, rpsB and rpsA gene sequence similarities calculated for Bifidobacterium taxa were 84.8, 85.2, 90.2 and 86.8%, respectively. Interestingly, the average value of the Average Nucleotide Identity among 67 type strains of the family Bifidobacteriaceae (84.70%) calculated based on values published recently was in agreement with the average pairwise similarity (84.6%) among 75 type strains of Bifidobacteriaceae family computed in this study using the concatenated sequences of four gene fragments. Similar to phylogenomic analyses, several gene sequence and phylogenetic analyses revealed that concatenated gene regions allow for classification of Bifidobacteriaceae strains into particular phylogenetic clusters and groups. Phylogeny reconstructed from the concatenated sequences assisted in defining two novel phylogenetic groups, the Bifidobacterium psychraerophilum group consisting of B. psychraerophilum, Bifidobacterium crudilactis and Bifidobacterium aquikefiri species and the Bifidobacterium bombi group consisting of B. bombi, Bifidobacterium bohemicum and Bifidobacterium commune.
Keywords: bakteriální proteiny; bakteriologické techniky; genotypizační techniky; Bacteriological Techniques; Bacterial Proteins; Actinobacteria; Multilocus Sequence Typing; multilokusová sekvenční typizace; Genotyping Techniques